1992
DOI: 10.1007/bf02347101
|View full text |Cite
|
Sign up to set email alerts
|

Buried seed population in the herbaceous lomas on Loma Ancon in the coastal desert of central Peru

Abstract: Herbaceous lomas in the Peruvian coastal desert of South America establish in spring, and its habitat is limited to the southern or southwestern slopes along the coast that are affected by thick fog. The time of appearance, the duration and the thickness of the fog vary greatly from year to year, so the lomas can grow only in habitats with enough water to sustain seed germination and plant growth. This paper studies the species composition and density of the buried seed population of the herbaceous lomas of Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…This, and their low seed production, the retention of seeds in the canopy, possible seed dormancy and short longevity might be some of the causes of their small numbers observed in the seed bank (Van Rooyen and Grobbelaar, 1982;Esler et al, 1992;Chambers, 1993;Bertiller, 1998). The contrasting pattern of the soil seed bank of annual compared with perennial species (small and numerous vs. large and scarce seeds) has previously been reported and associated with seed size and availability of safe sites for germination and plant establishment (Graham and Hutchings, 1988;Hedge et al, 1991;Ohga, 1991). Most of the annual species from the Succulent Karoo accumulate a persistent seed bank (Van Rooyen and Grobbelaar, 1982;De Villiers et al, 1994).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This, and their low seed production, the retention of seeds in the canopy, possible seed dormancy and short longevity might be some of the causes of their small numbers observed in the seed bank (Van Rooyen and Grobbelaar, 1982;Esler et al, 1992;Chambers, 1993;Bertiller, 1998). The contrasting pattern of the soil seed bank of annual compared with perennial species (small and numerous vs. large and scarce seeds) has previously been reported and associated with seed size and availability of safe sites for germination and plant establishment (Graham and Hutchings, 1988;Hedge et al, 1991;Ohga, 1991). Most of the annual species from the Succulent Karoo accumulate a persistent seed bank (Van Rooyen and Grobbelaar, 1982;De Villiers et al, 1994).…”
Section: Discussionmentioning
confidence: 91%
“…Similar lack of correspondence between vegetation and seed banks have been reported for agricultural habitats (Roberts and Stokes, 1966;Caixinhas et al, 1998), grassland communities (Milberg and Persson, 1994), forests (Granstrom, 1982), coastal plain forests (Matlack and Good, 1990), sand dunes (Planisek and Pippen, 1984) and desert environments (Khan, 1993;Aziz and Khan, 1996), and reflects such factors as absolute seed production, rate and depth of burial and loss of viability (Archibold, 1981). However, in some desert ecosystems the species composition of the seed bank proved to be similar to the standing vegetation (Henderson et al, 1988;Ohga, 1992). In general, Fenner (1985) suggested that similarity of vegetation and seed bank is greatest in frequently disturbed communities and that difference increases as succession progresses.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ellenberg (1959) found that patterns of root distribution in the sandy soils beneath different plant communities at Lachay corresponded well with the penetration of water. Buried seed pools in these lomas provide a reservoir of herb populations in years when fog moisture is too little to promote germination (Ohga 1982(Ohga , 1986. North of Lachay, the frequency and size of lomas formations drops steadily.…”
Section: Geomorphology and Vegetation Of The Coastal Peruvian Desertmentioning
confidence: 99%
“…Most studies of soil seed bank characteristics in arid or semiarid regions have focused mainly on land degradation (Reichman, 1984;MacMahon and Wagner, 1985;Price and Reichman, 1987;Wang and Liang, 1995;Pake and Venable, 1996;Guo et al, 1998Guo et al, , 1999López, 2003;Yan et al, 2005;Ma and Liu, 2008). In desert areas, the soil seed bank is usually composed of very small seeds, mainly annuals (Chambers and MacMahon, 1994;Gutterman 1994), and is characterised by enormous temporal and spatial fluctuations in seed density (Nelson and Chew, 1977;Price and Reichman, 1987;Kemp, 1989;Ohga, 1992;Pake and Venable, 1996;Price and Joyner, 1997;Gutiérrez et al, 1997;Guo et al, 1998Guo et al, , 1999Marone et al, 1998;López, 2003).…”
Section: Introductionmentioning
confidence: 99%